2016
DOI: 10.1080/15384101.2016.1252884
|View full text |Cite
|
Sign up to set email alerts
|

Altered apoptosis/autophagy and epigenetic modifications cause the impaired postimplantation octaploid embryonic development in mice

Abstract: Polyploids are pervasive in plants and have large impacts on crop breeding, but natural polyploids are rare in animals. Mouse diploid embryos can be induced to become tetraploid by blastomere fusion at the 2-cell stage and tetraploid embryos can develop to the blastocyst stage in vitro. However, there is little information regarding mouse octaploid embryonic development and precise mechanisms contributing to octaploid embryonic developmental limitations are unknown. To investigate the genetic and epigenetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Our study indicates that exposure to atrazine during oocyte maturation decreases the incidence of blastocysts and increases the number of apoptotic nuclei and expression of apoptosis-associated genes in porcine embryos. Although apoptosis is an in vivo or in vitro physiological process that occurs during preimplantation embryonic development [ 46 ], compared with early cleaving, there is a higher incidence of apoptosis during late cleavage, and therefore the less functional embryo shows reduced developmental capacity [ 47 ]. There is also evidence in the literature that the expression of genes related to apoptosis, such as Bcl-2 and Bax , is altered in embryonic culture [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that exposure to atrazine during oocyte maturation decreases the incidence of blastocysts and increases the number of apoptotic nuclei and expression of apoptosis-associated genes in porcine embryos. Although apoptosis is an in vivo or in vitro physiological process that occurs during preimplantation embryonic development [ 46 ], compared with early cleaving, there is a higher incidence of apoptosis during late cleavage, and therefore the less functional embryo shows reduced developmental capacity [ 47 ]. There is also evidence in the literature that the expression of genes related to apoptosis, such as Bcl-2 and Bax , is altered in embryonic culture [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…1B). Previous reports have indicated that octaploid embryos were absorbed and disappeared after implantation, leaving only empty decidua in mice (Wu et al, 2017). Wu and colleagues might have to failed to recover implanted octaploid embryos from the decidua by harvesting, because the polyploidized embryos were smaller than normal implanted embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these results, our experiments also showed that the developmental ratio decreased significantly in the hexadecaploid embryos. The development of octaploid embryos is affected by an increase in apoptosis, autophagy, and epigenetic modification (Wu et al, 2017), which indicates that higher the ploidy level, more severe the damage to embryogenesis from these intracellular alterations in the early development of a hexadecaploid embryo, compared to diploid and lesser ploidy embryos.…”
Section: Establishment and Characterization Of Hyperpolyploid Embryos By Repeated Electrofusionmentioning
confidence: 99%
“…If the number of cells in an embryo is artificially increased in the four-cell stage embryo, the ratio for the presence of the inner cell mass increases in tetraploid embryos (Wen et al, 2014). In mouse octaploid embryos, the number of cells with inner cell mass decreases significantly, and these cells also have more variety compared to that of diploid embryos in blastocysts (Wu et al, 2017). We have successfully established tetraploid embryonic stem cells (TESCs) from mouse tetraploid blastocysts; however, the efficiency of the establishment of TESCs (15%; Table 2) was quite low compared to that of ESCs (88 %; Table 2) (Imai et al, 2015).…”
Section: Absence Of Inner Cell Mass In the Hexadecaploid Embryomentioning
confidence: 99%